Study of an inertial piezoelectric energy harvester from a backpack. (3rd October 2019) - Chen, Fu; He, Ming; Wang, Sheng; Zhong, Xiang; Guan, Mingjie
Abstract: Harvesting energy from human motions for powering portable or wearable electronic devices is attracting attentions in recent years. In this paper, an inertial energy harvester based on a piezoelectric cantilever beam is investigated for harvesting energy from a backpack. Vibration levels in the backpack during walking or jogging were tested and analyzed. Theoretical analysis was explored to determine parameters of the harvester. The generated power of the cantilever beam was experimentally studied. The experimental results show that the harvester can achieve a power output of 43.64 μW with a single piezoelectric element.